Species identification and prevalence of gastrointestinal helminths in Indonesian native chickens, and its impact on egg production - Lili Zalizar; ARIS WINAYA; Abdul Malik; Wahyu Widodo; Suyatno Suyatno; Apriliana Devi Anggraini (Society for Indonesian Biodiversity, 2021)
Abstract. Zalizar L, Winaya A, Malik A, Widodo W, Suyatno, Anggraini AD. 2021. Species identification and prevalence of gastrointestinal helminths in Indonesian native chickens, and its impact on egg production. Biodiversitas 22: 4363-4369. Gastrointestinal parasite (GIP) infection is a severe problem of local chicken production, such as poultry and egg. Hence, the proper strategy to control the parasite invasion should be implemented regarding chicken productivity performance. Moreover, the existing environment is also essential in supporting chicken production. The study's objective was to determine the prevalence rate of the gastrointestinal helminths in four strains of Indonesian native chicken viz. Ranupane, Lokal Putih, Wareng, and Lurik, and the impact of the chicken egg production. A total of 280 chickens which were evaluated consisting of 70 birds from each strain, were tested for the prevalence of helminths eggs in a sample of feces and the effect on hen day production (HDP). The results showed that the percentage rates of infected chicken with helminths reached 56.43%, and the number of eggs per gram (EPG) in all four strains was considered moderate (115 EPG of feces). At the same time, the average of HDP per the four strains at 7 to 12 months was about 34.36-45.80%, which was in a normal range. The majority of helminths species found in examined native chicken were Ascaridia galli, Heterakis gallinarum, Raillietina spp., and Capillaria spp. The prevalence of GIP helminths did not negatively affect egg production in all four strains of chicken by moderately tolerant infections, and the HDP of chickens was normal.